1988
DOI: 10.5254/1.3536214
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Flow and Stress Fields in a Pressurized Mooney Viscometer

Abstract: The boundary conditions of rubber compounds on solid surfaces during extrusion has long been a subject of question. The concerns of Mooney on this topic date back 60 years. He continued to return to this question throughout his career. In more recent years Vinogradov and his coworkers have called attention to slip phenomena occurring in the extrusion of elastomers through dies. This is associated with fluctuating pressure losses which occur at the onset of extrudate distortion. Such behavior has also been obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similar biconical rotors were used in a subsequent work by Galvin and Whorlow (1975) on the shear stress growth of HDPE, LDPE, ethylene-vinyl acetate copolymer, while Best and Rosen (1968) adopted a biconical rotor with sharp edge in order to determine the flow curves of a natural rubber, and of a SBR, in a wide range of temperatures and shear rates. More recently, Montes et al (1988) Also used a variable speed Mooney viscometer equipped with a biconical rotor, emphasizing the role played by several operating variables (chamber pressure, grooves, etc. ) in avoiding slip at the wall.…”
Section: Nonlinear Viscoelasticitymentioning
confidence: 99%
“…Similar biconical rotors were used in a subsequent work by Galvin and Whorlow (1975) on the shear stress growth of HDPE, LDPE, ethylene-vinyl acetate copolymer, while Best and Rosen (1968) adopted a biconical rotor with sharp edge in order to determine the flow curves of a natural rubber, and of a SBR, in a wide range of temperatures and shear rates. More recently, Montes et al (1988) Also used a variable speed Mooney viscometer equipped with a biconical rotor, emphasizing the role played by several operating variables (chamber pressure, grooves, etc. ) in avoiding slip at the wall.…”
Section: Nonlinear Viscoelasticitymentioning
confidence: 99%
“…Studies of fluoroelastomer coated dies have also supported this (16). There is a long associated history of slippage of elastomers over metal sixfaces (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Vinogradov et al19, 20 have observed slip in polyisoprene and polybutadiene under similar conditions. It was also observed that elastomers at low applied pressures exhibited slip 21, 22…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that elastomers at low applied pressures exhibited slip. 21,22 There has been a limited literature on additives inducing slippage in the literature. We have already mentioned the work of Turner and Moore 8 with stearic acid in rubber compounds.…”
Section: Occurrence Of Slippagementioning
confidence: 99%